Pengaruh Undang-Undang Cipta Kerja terhadap Perilaku Dividen Perusahaan - Tony Agusta; Heru Tjaraka (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Investors have a goal when investing money in a company, namely to obtain income or returns (return) in the form of dividends or capital gains. There are three types of investors, namely aggressive investors, conservative investors, and moderate investors. This study aims to determine the effect of copyright law on dividend behavior of companies in Indonesia that are listed on the Indonesia Stock Exchange which are incorporated in the Kompas 100 index from 2017-2021. The research uses quantitative methods by comparing data for several years tested using classical assumption tests and data with descriptive statistical analysis. The results of the study show that the company that distributes the least dividends from the total net profit after tax is PT. Surya Citra Media Tbk (SCMA) in 2017 and 2021, while the company that distributes the most dividends from the total net profit after tax is PT. Bukit Asam Coal Mine Tbk. (PTBA) in 2021. Based on the time series analysis, it can be concluded that the work copyright law has a positive influence on the company's dividend policy by scoring the highest record dividend payout ratio since 2017 of 45.48%. Keywords: Dividend, Dividend Policy, Job Creation Law, Tax